Seletividade de tiametoxam em tratamento de sementes do algodoeiro para os predadores Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) e Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) - Sâmia, Rafaella Ribeiro (2017)
Thiamethoxam is an insecticide belonging to the group of neonicotinoids and has been used in the treatment of cotton seeds Gossypium hirsutum to control soil and shoot pests in their early stages of development. This compound presents high systemicity, being able to translocate throughout the plant and contaminate the pollen, floral and extrafloral nectar and cause damage to the natural enemies that feed on these resources. The objective of this work was to evaluate the effect of the treatment of cotton seeds with thiamethoxam on the predators Chrysoperla externa and Harmonia axyridis when larvae and adults fed on extrafloral nectar of cotton plants from seeds treated or not treated with this compound. Tests were performed where larvae or adults of the predators were housed in cages contain ing a cotton plant in the V2 stage. Adults were fed on Ephestia kuehniella eggs and artificial diet containing beer yeast and honey, the insects also had extrafloral nectar from cotton plants as food supplement. Survival, development and reproductive variables of exposed insects and their progeny were evaluated. From the C. externa larvae exposed (F0) to contaminated extrafloral néctar, there was a higher percentage of adult farats, and the survivors had a higher percentage of nonviable eggs. Larvae of the next generation (F1) presented longer development time and gave rise to a larger number of adult farats, with the survivors also having a lower percentage of viable eggs. Adults of C. externa exposed (F0) presented lower egg viability; the larvae of their progeny (F1) showed longer development time and adults generated from them showed lower fecundity and egg viability. In the experiments with H. axyridis, when larvae (F0) were exposed, only transgenerational negative effects were observed, with lower survival of pupae of the next generation (F1). Females from exposed adults (F1) presented lower weight and their progeny (larvae) had lower survival. It has been found that the treatment of cotton seeds with thiamethoxam has been detrimental to both predators. Alterations were observed in the development and reproduction of C. externa of both, those that fed on extrafloral nectar contaminated with insecticide as well as the insects of the next generation, being these effects more pronounced in their reproduction. For H. axyridis, only the development of the insects was harmed by thiamethoxam, and no changes were observed in the reproduction of the insects exposed to the treatment, not even in their progeny. It is necessary to investigate under field conditions if such effects are repeated and if they are capable of changing the population dynamics of these predators.